CUSTÓDIO DAM – THE GEOGENIC CONTRIBUTION TO SEDIMENT CHEMICAL COMPOSITION AND THE DETERMINATION OF GEOCHEMICAL REFERENCE VALUES FOR THE LAKES OF SE OF IRON QUADRANGLE - MG – BRAZIL - Pereira, V.; de Lena, J. C.; Roeser, H. M. P.; Nalini Jr., H. A.; Friese, K.; Morgenstern, P. (Geochimica Brasiliensis, 2012)